Mozambique's economic transformation: are efforts to streamline the fragmented aid landscape undermined for good? - Frank Vollmer (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
Mozambique is undergoing a strong transformation in its economic structure. This – mostly resource-led – transformation has not only attracted “new donors” such as China and Brazil; it has also impacted on efforts to make development assistance in Mozambique more effective by better harmonising Mozambique's aid system. For instance, the anticipated resource boom acts as a disincentive for the government to lead efforts to better streamline Mozambique's aid architecture, because it anticipates that its aid dependency will decline in the coming years. On the other hand, traditional donors with stagnating or declining aid shares do not want to exit this (potentially) emerging economy, despite the argument that their transaction costs offset the potential development outcomes from their aid provision (e.g. transaction costs for reporting that burden the administrative capacity of the government). Thus, opportunities aside, the economic transformation also bears challenges for development cooperation between Mozambique and its development partners. Efficiency gains through greater rationalisation are untapped as commercial and geo-strategic interests of the current 36+ donors present in Mozambique supplant development objectives. Based on a desk review and field research, the paper assesses how the economic transformation affects attempts of the traditional donor community, the emerging donors and the government of Mozambique to overcome donor proliferation and aid fragmentation in Mozambique.
Keywords: 330